2015
DOI: 10.5603/fm.2015.0116
|View full text |Cite
|
Sign up to set email alerts
|

Bite force and its correlation with long face in children and youth

Abstract: (Folia Morphol 2015; 74, 4: 513-517)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…In this respect our results confirm the data of Brown S. et al, (1995) and do not confirm the data of Quindini P. et al, (2017). Our results confirm those of Szymanska J. et al, (2015), who report that gender has only a weak effect on the average bite force on the right, and conclude that there is a lack of clinical correlation between bite force and gender. Other studies also do not find correlation between values of the masticatory function and gender at different age groups (11,19).…”
Section: Discussionsupporting
confidence: 91%
“…In this respect our results confirm the data of Brown S. et al, (1995) and do not confirm the data of Quindini P. et al, (2017). Our results confirm those of Szymanska J. et al, (2015), who report that gender has only a weak effect on the average bite force on the right, and conclude that there is a lack of clinical correlation between bite force and gender. Other studies also do not find correlation between values of the masticatory function and gender at different age groups (11,19).…”
Section: Discussionsupporting
confidence: 91%
“…Maximum bite force is one of the most important indicators of the functional situation of the masticatory system and its value is used to diagnose disorders of the musculoskeletal system of facial skeleton [20]. Maximum bite force is affected by skeletal craniofacial morphology, depending on the posterior/ anterior facial height ratio, vertical facial relationships, mandibular inclination and gonial angle [16,21,22].…”
Section: Resultsmentioning
confidence: 99%
“… 8 , 17 In contrast, some studies had shown a relatively small effect of age on bite force. 8 , 18 , 19 …”
Section: Discussionmentioning
confidence: 99%